Myths, masterplots and sexual harassment in Egypt. Issue 2 (4th March 2019) - Sadler, Neil
ABSTRACT: Formally a taboo subject, public sexual harassment in Egypt has received increased media attention since the 2011 revolution. The scholarly literature on the topic, however, remains thin, particularly with regard to the social mechanisms that sustain an environment permissive of street harassment. Drawing on the rape myths literature, this article argues that naturalised and stereotyped understandings of the causes and implications of street harassment provide discursive resources to excuse harassers and blame victims for the harassment they suffer. It argues, however, that these understandings are better understood as narrative masterplots to be contested than as myths to be debunked, emphasising that falsity and prejudicial impact must not be conflated. It concludes with recommendations for activism and future research, arguing that it may be more effective to promote alternative interpretive frames than attempt to directly challenge currently dominant understandings.